The influence of perceived behavioral control on online purchase intention with shopping motivation as the interventing variables in Tokopedia - Nainggolan, Gresita Stevani; Sijabat, Rosdiana (Institute of Computer Science (IOCS), 2023)
The shift in people's offline to online shopping preferences, as well as limited mobility due to the COVID-19 pandemic, has changed consumers' perspective on shopping from satisfaction to desire to satisfy their needs. The objective of this study is to examine the influence of hedonic and utilitarian motives in mediating perceived behavioral control on purchase intention. The method used in this study is quantitative research, with data analysis method structural equation modeling (SEM-PLS) and SmartPLS software version 4.0 to analyze data. The population of this study includes Tokopedia consumers located in Jakarta. There are 130 respondents who participated in this study. The results of this study show that perceived behavioral control has a significant influence on hedonic motivation, utilitarian motivation, and purchase intention. However, hedonic motivation does not have a significant influence on purchase intention. Otherwise, utilitarian motivations show a significant influence on purchase intentions. This study also reveals that perceived behavioral control on purchase intention through hedonic motivation does not have a significant impact, and perceived behavioral control on purchase intention through utilitarian motivation showed a significant impact.